PEMBERDAYAAN USAHA KECIL KOPRA DI DESA SAPA KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - RANTUNG, VINCENT; OGOTAN, MARTHA; TAMPI, GUSTAAF BUDI (JURNAL ADMINISTRASI PUBLIK, 2018)
Micro Enterprises Based on Law Number 20 of 2008 concerning MSMEs (Small and Micro Medium Enterprises) are productive businesses owned by individuals and / or individual business entities that meet the criteria of Micro Enterprises as stipulated in this Law. But there are problems of Kopra Small Business in Sapa Kecamata Tengah Village, South Minahasa Regency, which are unstable prices, declining prices, no capital assistance and copra processing facilities from the local government and decreased production due to copra farmers who are reluctant to produce copra because copra prices have not in accordance with the cost of living. To measure the success of copra research empowerment using the concept according to Edi Suharto, namely: Possibility, Strengthening, Protection, Improvement, and Maintenance. This study uses a qualitative method. The informants in this study were seven people. Data collection techniques used were interviews, observation and documentation. the results of research obtained in the copra business empowerment in the village of Sapa are done individually and on a household scale. Empowerment of the copra business in Sapa Village has received less attention from the government that there is no capital assistance and tools to support copra work directly from the government. It is not yet apparent that the village government’s efforts to voice the aspirations of copra farmers and entrepreneurs. The hope of the researchers is that the Sapa Village government to innovate propeople policies and programs such as being actively involved in copra business empowerment in Sapa Village so that copra can be developed into food, cosmetics and ingredients and oils such as Virgin coconut oil. the Sapa village government must dare to convey the aspirations of the copra farmer groups to the district level and there must be concrete actions from the government to provide capital and empowerment of copra into other derivative products. The need for economic institutions, such as village savings and loan cooperatives and the implementation of BUMDES must touch on every farmer group and copra businessman in Sapa Village. Keywords: Empowerment, of Society, Small Businesses.